Contextualizing the Use of Slang Words With References to Venom: Let There be Carnage Movie - Kadek Raihan; I Made Netra; Novita Mulyana (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2024)
This research entitled Slang words and Contextualization in Venom: Let There Be Carnage Movie, aimed to discuss the types of slang words and the contextualization the use of the slang word in the movie. The undergraduate thesis analysed the used of slang words in the conversations regarding the types and the contextualization of slang words. This research used the theory types of slang proposed by Allan and Burridge (2006) and the theory contextualization of slang proposed by Gumperz (1992) for the main theory. For the supporting theory used theory of sociolinguistics by Un Nisa (2019). The data of this study are from the utterances, words, and conversation occurred in the movie, in the form of slang words uttered by the characters dialogues. The analysed was use descriptive qualitative method. The results found that there were 5 slang words in the movie types and contextualization of slang, namely: Fresh and Creative, Flippant, Imitate, Acronym and Clipping. The result after analysing the movie, there were fourty six data in types and contextualization of slang. In the types and contextualization of slang, the highest type was flippant slang type and the lowest was acronym type.